2000
DOI: 10.1038/sj.gene.6363686
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for linkage in the promoter region of the inducible nitric oxide synthase gene (NOS2) in a Danish type 1 diabetes population

Abstract: Exposure of human pancreatic islets to a mixture of cytokines induces expression of inducible nitric oxide synthase (iNOS), impairs beta-cell function and induces apoptosis. Exposing human islets to high amounts of NO from chemical NO-donors causes DNA strand breaks and mitochondrial damage, suggesting that NO is deleterious to human beta-cells. Hence, we consider the gene encoding iNOS in beta-cells, NOS2, a candidate gene for type 1 diabetes in humans. In the present study we have tested three identified pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…This is consistent with former studies where it has always been shown nonpolymorphic in Caucasian populations. 7,13 Regarding the bi-allelic TAAA marker (for methods see Glenn et al 14 13,14 and confirm that the (TAAA) n marker is not very informative in detecting association due to its limited degree of polymorphism. The multiallelic (CCTTT) n repeat is on the contrary an attractive disease-causing candidate, being a highly polymorphic marker with a recently suggested effect in NOS2 transcription.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…This is consistent with former studies where it has always been shown nonpolymorphic in Caucasian populations. 7,13 Regarding the bi-allelic TAAA marker (for methods see Glenn et al 14 13,14 and confirm that the (TAAA) n marker is not very informative in detecting association due to its limited degree of polymorphism. The multiallelic (CCTTT) n repeat is on the contrary an attractive disease-causing candidate, being a highly polymorphic marker with a recently suggested effect in NOS2 transcription.…”
Section: Resultsmentioning
confidence: 78%
“…The (TAAA) n and (CCTTT) n ms at the NOS2 promoter region have been analysed for association with the susceptibility to IDDM, other autoimmune and complex genetic condition, in which iNOS mediated NO production has been implicated, and similar to us, no linkage of the two NOS2 promoter microsatellites was observed in a large collection of families. 13 Likewise, no association was identified when TAAA-CCTTT haplotypes were constructed and analysed in our RA case-control cohort. Of note no linkage disequilibrium (LD) was found between the two markers.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…These single nucleotide polymorphisms seem to be ethnically specific, taking into account the results of the previous studies [27]. As to the Romanian population, there is no study with respect to the iNOS2 -2087A>G polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic milieu as long as NOS3 expression is low, the induction of NOS2 expression may occur in an attempt to achieve homeostasis, being crucial in preventing or delaying pathological alterations in the microcirculation (Warpeha & Chakravarthy 2003). In studies of diabetic complications, as DR and DN, influenced by vascular functional disturbances, the increased NO formation via NOS2 expression has been reported (Johannesen et al, 2000a). In human NOS2A gene has been identified a large number of polymorphisms.…”
Section: Nos2a Genementioning
confidence: 99%